Effect of inter-plies on the short beam shear delamination of steel/composite hybrid laminates. Issue 12 (15th October 2019) - Hader-Kregl, Laura; Wallner, Gernot M.; Kralovec, Christoph; Eyßell, Carola
ABSTRACT: Interlaminar shear test methods (ILS) were implemented to characterize the delamination behavior of asymmetric steel/carbon fiber reinforced plastic (CFRP) hybrids. To improve the delamination behavior thermoplastic inter-plies were inserted between CFRP and steel. Supported by optical strain measurement the maximum shear stress (τMAX ), the shear stress at interfacial delamination (τIF ) and the shear stress at large-scale CFRP ply delamination τD were evaluated. The significant effect of inter-plies on the adhesion was best reflected by the shear stress value at interfacial delamination. Finite element analysis of the actual shear stress distribution in an asymmetric hybrid sample without inter-ply revealed that the calculated shear strength is just slightly overestimated compared to the standardized evaluation procedure.